Impact of first-wave COronaVIrus disease 2019 infection in patients on haemoDIALysis in Alsace: the observational COVIDIAL study. Issue 8 (2nd September 2020) - Keller, Nicolas; Chantrel, François; Krummel, Thierry; Bazin-Kara, Dorothée; Faller, Anne Laure; Muller, Clotilde; Nussbaumer, Thimothée; Ismer, Manfred; Benmoussa, Abdellatif; Brahim-Bouna, Mohamed; Beier, Stéphanie; Perrin, Peggy; et al.
Abstract: Background: There are only scarce data regarding the presentation, incidence, severity and outcomes of coronavirus disease 2019 (COVID-19) in patients undergoing long-term haemodialysis (HD). A prospective observational study was conducted in eight HD facilities in Alsace, France, to identify clinical characteristics of HD patients with COVID-19 and to assess the determinants of the risk of death. Methods: All HD patients tested positive for COVID-19 from 5 March to 28 April 2020 were included. Collected data included patient characteristics, clinical features at diagnosis, laboratory data, treatments and outcomes. Results: Among 1346 HD patients, 123 tested positive for COVID-19. Patients had a median age of 77 years (interquartile range 66–83), with a high number of comorbidities (3.2 ± 1.6 per patient). Symptoms were compatible in 63% of patients. Asthenia (77%), diarrhoea (34%) and anorexia (32%) were frequent at diagnosis. The delay between the onset of symptoms and diagnosis, death or complete recovery was 2 (0–5), 7 (4–11) and 32 (26.5–35) days, respectively. Treatment, including lopinavir/ritonavir, hydroxychloroquine and corticosteroids, was administered in 23% of patients. The median C-reactive protein (CRP) and lymphocyte count at diagnosis was 55 mg/L (IQR 25–106) and 690 Ly/µL (IQR 450–960), respectively. The case fatality rate was 24% and determinants associated with the risk of death were body temperature hazard ratio [HR] 1.96 [95% confidence interval (CI) 1.11–3.44]; P = 0.02 and CRP at diagnosis [HR 1.01 (95% CI 1.005–1.017); P < 0.0001]. Conclusions: HD patients were found to be at high risk of developing COVID-19 and exhibited a high rate of mortality. While patients presented severe forms of the disease, they often displayed atypical symptoms, with the CRP level being highly associated with the risk of death.